1982
DOI: 10.1159/000117876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lithium on Circadian Neurotransmitter Receptor Rhythms

Abstract: Chronic lithium administration significantly changes characteristics of the circadian rhythms in rat brain α- and β-adrenergic, muscarinic acetylcholine, dopamine, opiate, and benzodiazepine receptors. There are changes in the timing of the peak number of receptors (phase-position), in the amplitude of the rhythms, and in the 24-hour mean number of receptors. The circadian rhythm in the number of forebrain α- and β-adrenergic and benzodiazepine receptors is abolished. The phase-position of forebrain acetylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…1). This result is consistent with some previous reports (13)(14)(15), whereas it is inconsistent with others in which no significant change (16)(17)(18)(19)(20) or an increase (21) in densi ties of /3-adrenergic receptors by long-term lithium administration was reported. While the precise cause of this discrepancy is unknown, the difficulty in detecting a relatively small amount of decrease in density of fi-adreno ceptors induced by long-term lithium treat ment was pointed out (15).…”
Section: Discussionsupporting
confidence: 67%
“…1). This result is consistent with some previous reports (13)(14)(15), whereas it is inconsistent with others in which no significant change (16)(17)(18)(19)(20) or an increase (21) in densi ties of /3-adrenergic receptors by long-term lithium administration was reported. While the precise cause of this discrepancy is unknown, the difficulty in detecting a relatively small amount of decrease in density of fi-adreno ceptors induced by long-term lithium treat ment was pointed out (15).…”
Section: Discussionsupporting
confidence: 67%
“…In the rat, there is a circadian variation in tyrosine hydroxylase activity, DA turnover [26], DA levels [26,27] and number of DA receptors [28][29][30]. A change in receptor number could explain our present findings of a difference in yawning response depending on time of day of Apo administration.…”
Section: Discussionsupporting
confidence: 46%
“…Halmi et al [1972] demonstrated that in healthy persons the circadian variation of serum cortisol was smaller dur ing lithium administration than when they were receiving a placebo -due to the lower morning cortisol levels while on lithium. Recently, some studies in animals have shown that lithium delayed hormone circadian rhythms [McEachron et al, 1982] and that cholinergic and adren ergic receptor rhythms were also delayed or decreased in their amplitudes by lithium [Kafka et al, 1982;Wehrand Wire-Justice, 1982].…”
Section: Introductionmentioning
confidence: 99%